Plants cope with fluctuating light by frequency-dependent nonphotochemical quenching and cyclic electron transport - Niu, Yuxi; Lazár, Dušan; Holzwarth, Alfred R; Kramer, David M; Matsubara, Shizue; Fiorani, Fabio; Poorter, Hendrik; Schrey, Silvia D; Nedbal, Ladislav (The New phytologist, 2023)
In natural environments, plants are exposed to rapidly changing light. Maintaining photosynthetic efficiency while avoiding photodamage requires equally rapid regulation of photoprotective mechanisms. We asked what the operation frequency range of regulation is in which plants can efficiently respond to varying light. Chlorophyll fluorescence, P700, plastocyanin, and ferredoxin responses of wild-types Arabidopsis thaliana were measured in oscillating light of various frequencies. We also investigated the npq1 mutant lacking violaxanthin de-epoxidase, the npq4 mutant lacking PsbS protein, and the mutants crr2-2, and pgrl1ab impaired in different pathways of the cyclic electron transport. The fastest was the PsbS-regulation responding to oscillation periods longer than 10 s. Processes involving violaxanthin de-epoxidase dampened changes in chlorophyll fluorescence in oscillation periods of 2 min or longer. Knocking out the PGR5/PGRL1 pathway strongly reduced variations of all monitored parameters, probably due to congestion in the electron transport. Incapacitating the NDH-like pathway only slightly changed the photosynthetic dynamics. Our observations are consistent with the hypothesis that nonphotochemical quenching in slow light oscillations involves violaxanthin de-epoxidase to produce, presumably, a largely stationary level of zeaxanthin. We interpret the observed dynamics of photosystem I components as being formed in slow light oscillations partially by thylakoid remodeling that modulates the redox rates.
Keywords: Photosynthesis; Chlorophyll; Photosystem II Protein Complex; Membrane Proteins; cyclic electron transport; proteiny huseníčku; regulation; světlo; Light-Harvesting Protein Complexes; frequency analysis; mutace; chlorofyl; Arabidopsis Proteins; Photosynthetic Reaction Center Complex Proteins; Light; Arabidopsis; fotosystém II (proteinový komplex); nonphotochemical quenching; fotosyntetická reakční centra (proteinové komplexy); transport elektronů; světlosběrné proteinové komplexy; membránové proteiny; photosynthetic oscillation; Mutation; fotosyntéza; Electron Transport